On Possibility of Universally Composable Commitments Based on Noisy Channels - Dowsley, Rafael; Müller-Quade, Jörn; Nascimento, Anderson C. A. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2008)
Universally Composable (UC) Commitment is a strong notion that guarantees security even when the commitment protocol is composed with arbitrary protocols running many of their copies in parallel. It is impossible to implement a protocol that realizes UC Commitment without set-up assumptions. However, it has been implemented using such assumptions as common reference string, certified public keys and random oracles. In this paper we prove that the existence of a binary symmetric channel between the parties makes possible the accomplishment of UC Commitment.